Evaluation of existing knowledge, perceptions and practices of diagnostic imaging among non-radiologist physicians in Makurdi, North-Central Nigeria - Chia, Daniel M.; Mohammad, Hameed; Ugande, Alexis A.; Iorpagher, Paul K. (International Journal of Research in Medical Sciences, 2022)
Background: Despite the restricted diagnostic imaging knowledge, perceptions, and practices of non-radiologist physicians, the significance of radiology in establishing and verifying diagnoses in medicine is expanding globally. We aimed to evaluate existing diagnostic imaging knowledge, perceptions, and practices among referring non-radiologist physicians, identify aspects that are beneficial but substantially inconsistent, and determine those that can be improved. Methods: A 3-month cross-sectional study, utilizing structured questionnaire, was responded to by physicians at Benue State University Teaching Hospital (BSUTH), Makurdi. Descriptive statistics were used for the statistical analysis and results presented as tables and figures. Statistical significance was determined at p=0.05. Results: We recruited 137 physicians, aged 26 to 52 years, consisting of 111 (81.0%) males and 26 (19.0%) females. Majority,79 (57.7%) of respondents did not know which imaging modality; chest computed tomography (CT-chest) or chest X-rays (CXR), presented higher ionizing radiation hazards. Few 54 (39.4%) desired the radiologists’ lifestyle, while less than half 62 (45.3%) believed that any referral involving radiation risks should be justified. The ratings for diagnostic imaging knowledge, perceptions and practices were consecutively excellent, 124 (90.5%), optimistic 5 (3.6%) and healthy 19 (13.9%). No statistically significant correlations were found between knowledge and perceptions, knowledge and practices, or perceptions and imaging practices. Conclusions: Non-radiologist physicians demonstrated excellent knowledge but pessimistic perceptions and unhealthy imaging practices. A misconception existed over which modality, CT-chest or CXR, presented greater radiation risks. A few desired the radiologists’ lifestyles while a minority sought justification for radiation-risky investigations. These aspects were beneficial but inconsistent, necessitating improvements through multidisciplinary clinical interactions.